Prevalencia y factores asociados a caídas en adultos mayores que viven en la comunidad - Lavedán Santamaría, Ana (Aten Primaria, 2015)
OBJECTIVE: To estimate the prevalence of falls and to identify their associated factors in community-dwelling elderly. DESIGN: A descriptive, cross-sectional study. SETTING: Primary Health Care, Lleida. PARTICIPANTS: Six hundred and forty people aged 75 and older were included, in possession of a health card and living in single-family houses, through random sampling. Main measurements Data source comes from the survey of frailty in Lleida (FRALLE Survey). The variables used were the occurrence of falls, sociodemographic factors, health status, quality of life related to health and fear of falling. RESULTS: The prevalence of falls was 25.0% (95% CI 24.8-25.1). After multivariate analysis, basic disability (OR = 2.17; 95% CI 1.32-3.58), depressive symptoms (OR = 1.67; 95% CI 1.07-2.59) and fear of falling (OR = 2.53; 95% CI 1.63-3.94) were the only factors independently associated with falls in the last year. CONCLUSIONS: One out of 4 older people reported at least a fall in the last year. This study demonstrates that fear of falling, depressive symptoms and basic disability are independent variables associated with previous falls. These 3 factors can lead to a flattering spiral of falling and may be potential targets for effective functioning in the context of falls.